Pengelolaan Ekosistem dan Daya Dukung Lingkungan Kawasan Wisata Bahari Mangrove Karongsong Indramayu - Adhitiowasis, Aryo; Maryani, Enok; Andari, Rini (Journal of Tourism and Creativity, 2022)
Karongsong Village is one of the villages in the mangrove rehabilitation area which is still well maintained. In the beginning, the management of mangrove planting there was carried out by the local community in collaboration with PT Pertamina. The beginning of this Mangrove Ecotourism in Karongsong was the occurrence of abrasion on Karongsong Beach from 1983 to 2022, which in the future could cause a Tsunami or subsequent abrasion. So to anticipate this, beach rehabilitation and the creation of Mangrove Ecotourism are made to avoid or minimize future Tsunamis. But apparently, after the pandemic period, Mangrove Ecotourism in Karongsong was not maintained and not well managed. Due to the large number of damage to facilities, dead animals, and so on. Therefore, the author wants to try to increase the potential of Mangrove Ecotourism by asking for support from the local government. So that they take appropriate action in preserving the ecotourism. So that Mangrove Ecotourism in Karongsong can function as usual and as it should.